2010
DOI: 10.4097/kjae.2010.59.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pain with the injection of microemulsion propofol: a comparison of a combination of lidocaine and ketamine with lidocaine or ketamine alone

Abstract: BackgroundAquafol, a microemulsion propofol, causes more severe and frequent pain on injection than propofol. The purpose of this study was to compare a combination of lidocaine and ketamine on aquafol-induced pain with lidocaine or ketamine alone during the induction of anesthesia.MethodsIn this prospective, randomized, double-blinded study, 130 healthy patients who were undergoing elective surgery under general anesthesia were enrolled. The patients received IV lidocaine 40 mg plus ketamine 25 mg (Group LK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…There exists a basic hypothesis about pain transmission that is sensitization of spinal cord by activating glutamate and aspartate in N-Methyl-D-aspartate (NMDA) receptors (7). Recognition of NMDA receptors and the roles they play in reducing the patients’ pain causes a novel evolution in consumption of such receptor antagonists like ketamine (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…There exists a basic hypothesis about pain transmission that is sensitization of spinal cord by activating glutamate and aspartate in N-Methyl-D-aspartate (NMDA) receptors (7). Recognition of NMDA receptors and the roles they play in reducing the patients’ pain causes a novel evolution in consumption of such receptor antagonists like ketamine (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies1,2 have shown that effective analgesia reduces postoperative complications, pain is often overlooked and not adequately controlled 3. It has been shown that many excitatory substances are released by painful impulses which stimulate receptors to cause pain 3,4. The principal phenomenon in inflammatory pain transmission is sensitization of the spinal cord, with an active contribution from glutamate and aspartate amino acids at the N-methyl-dimethyl-aspartate (NMDA) receptor 4…”
Section: Introductionmentioning
confidence: 99%
“…Artan dozlarda lidokain uygulamasının ağrıyı daha yüksek oranda azalttığına dair çalışmalar vardır (14) . Lidokaine fentanil (15) , remifentanil (16,17) , ketamin (18,19) , flurbiprofen (5) eklenmesinin de etkili olduğunu söyleyen yayınlar mevcuttur. Massad ve ark.…”
Section: Discussionunclassified